Antibiotic-resistant Escherichia coli bacteria, including strains with genes encoding the extended-spectrum beta-lactamase and QnrS, in waterbirds on the Baltic Sea Coast of Poland - Literak, Ivan; Dolejska, Monika; Janoszowska, Dagmar; Hrusakova, Jolana; Meissner, Wlodzimierz; Rzyska, Hanna; Bzoma, Szymon; Cizek, Alois (Applied and environmental microbiology, 2010)
Individual cloacal swabs of mallards (Anas platyrhynchos) and of herring gulls (Larus argentatus), as well as samples of waterbird feces obtained in 2008 and 2009, were cultivated for Escherichia coli. Isolates of E. coli were tested for susceptibilities to 12 antimicrobial agents by the disk diffusion method. Moreover, the samples were subcultivated on MacConkey agar (MCA) containing cefotaxime (2 mg liter(-1)) to detect E. coli with extended-spectrum beta-lactamase (ESBL) and subsequently on MCA supplemented with ciprofloxacin (0.05 mg liter(-1)) and MCA with nalidixic acid (20 mg liter(-1)) to isolate fluoroquinolone-resistant E. coli. PCR was used to detect specific antibiotic resistance genes. We found 9 E. coli isolates producing ESBL with bla genes: bla(CTX-M-1) (6 isolates), bla(CTX-M-9) plus bla(TEM-1b) (1 isolate), bla(CTX-M-15) plus bla(OXA-1) (1 isolate), and bla(SHV-12) (1 isolate). In the isolate with bla(CTX-M-15), the gene aac(6)-Ib-cr was also detected. The bla genes were harbored by transferable plasmids of the IncN and IncI1 groups. Nine quinolone-resistant E. coli isolates with qnrS genes were found and characterized. The gene qnrS was associated with a Tn3-like transposon on the IncX1 plasmid together with bla(TEM-1) in two isolates. The gene qnrS was also harbored by conjugative plasmids of the IncN and IncX2 groups. Even if populations of wild birds are not directly influenced by antibiotic practice, we have demonstrated that antibiotic-resistant E. coli strains, including strains with various ESBL and qnrS genes, are found in the feces of wild birds on the coast of the Baltic Sea in Poland.
Keywords: Microbial Sensitivity Tests; feces; Genes, Bacterial; Polsko; mikrobiální testy citlivosti; Escherichia coli; Charadriiformes; antibakteriální látky; zvířata; plazmidy; Poland; Culture Media; Oceans and Seas; kultivační média; Feces; beta-laktamasy; Cloaca; Anseriformes; Anti-Bacterial Agents; Drug Resistance, Bacterial; bakteriální geny; beta-Lactamases; bakteriální léková rezistence; Animals; kloaka; Plasmids; oceány a moře